2009
DOI: 10.1007/s10554-009-9506-6
|View full text |Cite
|
Sign up to set email alerts
|

FDG–PET can distinguish inflamed from non-inflamed plaque in an animal model of atherosclerosis

Abstract: The presence of activated macrophages is an important predictor of atherosclerotic plaque rupture. In this study, our aim was to determine the accuracy of (18)F- fluorodeoxyglucose (FDG) microPET imaging for quantifying aortic wall macrophage content in a rabbit model of atherosclerosis. Rabbits were divided into a control group and two groups post aortic balloon injury: 6 months high-cholesterol diet (HC); and 3 months HC followed by 3 months low-cholesterol diet plus statin (LCS). In vivo and ex vivo microPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…Inhibiting NF-κB using Bay 11-7055, an inhibitor of inhibitor of κB kinase, significantly reduced both the number of NF-κB-immunopositive nuclei ( Figure 6A) and TF protein production ( Figure 6B). Staining 23 Macrophages and granulocytes express glucose transporter 1 and hexokinase II in lung inflammatory lesions. 18 F-FDG uptake correlates with the degree of inflammation 24 and lipopolysaccharide enhances 18 F-FDG uptake by isolated human monocyte-macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting NF-κB using Bay 11-7055, an inhibitor of inhibitor of κB kinase, significantly reduced both the number of NF-κB-immunopositive nuclei ( Figure 6A) and TF protein production ( Figure 6B). Staining 23 Macrophages and granulocytes express glucose transporter 1 and hexokinase II in lung inflammatory lesions. 18 F-FDG uptake correlates with the degree of inflammation 24 and lipopolysaccharide enhances 18 F-FDG uptake by isolated human monocyte-macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In rabbit models, FDG was shown to be taken up by macrophage-rich atherosclerotic lesions in the aortic arch, and there was a correlation between FDG accumulation in the plaque with local macrophage density [15][16][17][18]. In humans, accumulation of 3H-deoxyglucose was shown in macrophage-rich areas of freshly isolated human carotid plaques [19] along with a significant correlation between FDG PET activity in carotid plaques and macrophage staining from the corresponding histologic sections of post-endarterectomy samples [20].…”
Section: Plaque Fdg Uptake Correlates With Macrophage Density and Infmentioning
confidence: 99%
“…Recent studies reported on the potential use of intravascular ultrasonography, CT angiography, MRI, and metabolic 18 F-fluorodeoxyglucose (FDG) imaging with positron emission tomography (PET) for this purpose [5][6][7][8]. A combined functional and structural whole-body imaging will likely afford the best potential for visualizing coronary atherosclerosis and plaque inflammation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] However, because FDG is taken up by any metabolically active tissues, including those surrounding atherosclerotic plaques (such as fat, muscles, and lymph nodes), concerns have been raised about the specificity of this tracer for imaging inflammatory cells. Indeed, Davies et al 32 showed that in vivo FDG uptake in atherosclerotic lesions of rabbit aorta does not correlate with macrophage density. They reported no significant difference in FDG uptake between rabbits with highly inflamed aortic walls, those with low levels of inflammation, or controls.…”
mentioning
confidence: 99%
“…They reported no significant difference in FDG uptake between rabbits with highly inflamed aortic walls, those with low levels of inflammation, or controls. 32 Moreover, recent clinical data on FDG PET showed an inconsistent correlation between FDG uptake and intraplaque inflammation, ranging from significantly high, 7 medium, 33 to very poor correlation coefficients. 34 Conversely, a high degree of choline uptake in macrophage-rich areas of murine atherosclerotic lesions has been observed with choline in autoradiographic studies, 20 suggesting that 18 F-FCH may provide a more specific tracer to assess active macrophage infiltration.…”
mentioning
confidence: 99%